A mixed-integer linear programming model for aggregating multi–criteria decision making methods - Pala, Osman (Decision Making: Applications in Management and Engineering, 2022)
Selecting an MCDM method to use in any decision-making problem is always a difficult issue regarding that there is no agreement generally on which method is the most appropriate one. This paper addressed a proposal of a hybrid approach for this problem. Under the assumption that there is no superiority among well-established and accepted MCDM methods, we defined a maximin strategy based on the fact that the lowest correlation between MCDMs and the proposed hybrid approach in terms of alternative rankings should be as high as possible. Even though MCDM methods often rank the alternatives differently, many methods perform similar ranking due to sharing alike mathematical operations. To avoid positive bias towards these methods in an integrated approach, we focused on a prioritizing scheme that supports different rankings. This prioritizing scheme also contributed to hinder the problem of selecting MCDMs with constraining the compound effect of similar rankings. We developed a hybrid decision-making model combining different MCDM methods with prioritizing them by using a binary integer linear programming model. We compared the proposed approach with some well-known prioritizing methods and the results revealed that the proposed approach produced better outcomes in obtaining the desired outputs.